2009
DOI: 10.1016/j.jacc.2009.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Modifiers of Long-Term Survival in Heart Failure

Abstract: Objective To identify genetic modifiers of β-blocker (BB) response and long-term survival in heart failure (HF). Background Differences in BB treatment effect between Caucasians and African Americans with HF have been reported. Methods Prospective cohort study of 2,460 patients (711 African American; 1,749 Caucasian) enrolled between 1999 and 2007. 2039 (81.7%) were treated with BB. Each was genotyped for β1-adrenergic receptor (ADRB1) Arg389>Gly and G-protein receptor kinase 5 (GRK5) Gln41>Leu polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 53 publications
11
93
0
2
Order By: Relevance
“…Because the HSPB7 heart failure-associated SNPs do not alter protein coding or cardiac gene expression, we hypothesized that the HSPB7 risk variants marked heart failure risk alleles within the broader genetic region. Accordingly, we resequenced all 19 coding exons and intron-exon boundaries of the adjacent CLCNKA gene in 1,742 DNA samples from the Cincinnati Heart Failure Study (18,19). (Detailed clinical characteristics of the study populations are in Table S1.)…”
Section: Resultsmentioning
confidence: 99%
“…Because the HSPB7 heart failure-associated SNPs do not alter protein coding or cardiac gene expression, we hypothesized that the HSPB7 risk variants marked heart failure risk alleles within the broader genetic region. Accordingly, we resequenced all 19 coding exons and intron-exon boundaries of the adjacent CLCNKA gene in 1,742 DNA samples from the Cincinnati Heart Failure Study (18,19). (Detailed clinical characteristics of the study populations are in Table S1.)…”
Section: Resultsmentioning
confidence: 99%
“…To catalog nucleotide variations within the 4 target gene exons, we amplified and resequenced 5 loci covering 9.4 kb of nonamplified genomic DNA archived from 2,606 individuals -1,742 Caucasians and 864 African Americans -who had participated in a longitudinal study of systolic heart failure (20). The coding regions for ADRA1A, ARDB2, HSPB7, and PLN were comprehensively examined ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that patients receiving beta-blockers with the Gln41Gln genotype but Leu41 carriers exhibited improvement in survival compared to Glu41 carriers (79). The other larger study did not confirm this (80).…”
Section: Beta-blockersmentioning
confidence: 86%